Vulvar Squamous Cell Carcinoma In A Horse : A Case Report - S.B. Tadavi, Madhuri Hedau1 , R. S. Ingol Suvarna Sonwane3 , (International Journal of Scientific Research and Management (IJSRM), 2017)
Formalin fixed tumor mass from vulva of mare was received from TVCC, PGIVAS, Akola for histopathological examination and diagnosis. Clinical examination findings reported were large ulcerated, neoplastic mass located at the unpigmented areas on the mucocutaneous junction of the vulva. Histopathologically, the ulcerated growth showed irregular cords of neoplastic squamous epithelial cells surrounded by connective tissue stroma. The tumor showed formation of keratin pearls in the centre of cords and presence of few mitotic figures. The neoplastic squamous cells showed large hyperchromatic nuclei. On the basis of histopathological examination, the present case was diagnosed as vulvar squamous cell carcinoma.